Effect of Basil (Ocimum americanum L.) Proportion on Physical and Organoleptical Properties of Basil Cracker - Yoga Pratama; Tsurayya Ulfah; Valentinus Priyo Bintoro (Journal of Applied Food Technology, 2018)
Basil contains flavonoid, saponin, tannin, and essential oils namely sineol and eugenol. Basil has been known as appetite stimulant, laxative, fragrance, and breast milk stimulator. This study aimed to determine the effect of basil addition to linear expansion, crispiness, color, and organoleptic of basil cracker. Complete Randomized Design was used in this research with 4 treatments and 5 replications i.e. T1 (10% basil, 90% tapioca), T2 (15% basil, 85% tapioca), T3 (20% basil, 80% tapioca), T4 (25% basil, 75% tapioca). Linear expansion was measured using ruler, hardness/crispiness using texture analyzer, color using digital colormeter, and organoleptic testing was done by 25 panelists. The research showed that basil cracker had linear expansion of 166-235%; hardness of 1264.8-1837.6 gF; L* value of 22,47-40,40 and a* value of -20.73 to -12.67. Variation of basil proportion gave significant effects to linear expansion, crispiness, and color of basil cracker. The best treatment was T2 (15% basil, 85% tapioca) because it had high linear expansion and bright color, was crispy, and preferred by panelists.